PROSEDUR PENYIMPANAN BAHAN MAKANAN DI KITCHEN GARDIN BISTRO PATTISSIERA PETITENGET BALI - Ida Ayu Karina Putri; Dewa Nyoman Sumardiana,; I Ketut Sutapa (HARMONY HOSPITALITY, 2023)
This study aims to determine the procedures for storing foodstuffs, the obstacles encountered in the procedures for storing foodstuffs and the efforts made to overcome the problems of storing foodstuffs at Kitchen Gardin Bistro Pattissiera. The method of data collection was carried out by conducting observations, interviews, and documentation using qualitative descriptive analysis techniques, namely describing and describing the procedures for storing food ingredients at Kitchen Gardin Bistro Pattissiera. Constraints faced in the Food Storage Procedure at Kitchen Gardin Bistro Pattissiera are the lack of storage space so that overloads often occur, the storage temperature is often damaged, and the first in first out system has not been implemented. Efforts are being made to limit the ordering of goods, implement a first in first out system, and improve the temperature of the storage room. The suggestion is to immediately realize what has been conveyed by the resource person.